Comparative Perception of Undergraduate Medical and Dental Students between Case-Based Learning and Problem-Based Learning in Karachi - Syed M. Abdullah Salman, Talal Bin Taheer, Shaima Sultana Memon, Zafar Iqbal, Urooj Yahya, Urosa Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Teaching methodologies that govern self-directed learning skills include problem-based learning (PBL) and case-based learning (CBL). Both undergraduate and graduate curriculum in Pakistan medical colleges frequently employ one or the other, depending on the situation. The objective of our research was to contrast PBL and CBL in the undergraduate medical curriculum based on the perceptions of the students who had seen this change in learning methodologies. Method: It was a cross-sectional study conducted between March and June 2022 at a medical university in Karachi. A closed ended self-administered questionnaire with fourteen questions was prepared and distributed to 150 student. The responses to the questions were dichotomous in favor of problem based learning. Third and second year MBBS and BDS students of both genders, and socioeconomic status were included in this study. Student responses on the usefulness of PBL were obtained on a 5-point Likert scale, and results were compared using the chi square test. Result: In general, the learners were positive about all of the items in favor of PBL, such as self-directed learning, critical thinking, identifying objectives, identifying knowledge gaps, and improved problem-solving skills. Conclusion: Problem based learning is a preferred instructional strategy as compared to case base learning from perspective of the student. Keywords: Problem-based learning (PBL), Case-based learning (CBL), Medical students, Dental students, Perception.